Arthur J. Goldberg papers - Goldberg, Arthur J.; Goldberg, Dorothy Kurgans
Correspondence, family papers, transcripts of an oral history interview, speeches, writings, draft opinions, memoranda, notes, professional and subject files, and other papers pertaining to Goldberg's service as secretary of labor in the administration of John F. Kennedy, associate justice in the U.S. Supreme Court, and U.S. ambassador to the United Nations; his law practice in New York, N.Y., and Washington, D.C.; and his role as chairman of the U.S. delegation to the Conference on Security and Cooperation in Europe, Belgrade, Yugoslavia, 1977-1978. Also includes material on his World War II activities with the U.S. Office of Strategic Services, his work as legal counsel to the United Steelworkers of America and the AFL-CIO, and his unsuccessful campaign for governor of New York in 1970. Other topics include organized labor and local politics in Chicago, Ill., national politics, international relations, constitutional law, shipbuilders and steelworkers' strikes, Israel and the Jewish community, tension in the Middle East and South Africa, conflict between India and Pakistan, North Korea and the Pueblo incident, and nuclear proliferation. Also documented is Goldberg's legal representation of Kaiser Industries Corporation, the Denver Post, and baseball player Curt Flood in cases concerning corporate social responsiblity and free agency for baseball players.
Papers of his wife, Dorothy Kurgans Goldberg, comprise correspondence, diaries, speeches and writings, and other papers documenting her activities as an author, lecturer, and wife of an ambassador and prominent public official. Includes notes and journal kept by her as a member, along with her husband, of the U.S. delegation to meetings of the Conference on Security and Cooperation in Europe. Also includes material on her work in promoting public schools in Washington, D.C., the National School Volunteer Program, and the U.S. President's Task Force on International Education. Topics include art, Jews, voluntarism, and women's issues.
Correspondents include Emery Bacon, David L. Bazelon, Arnold Beichman, William Benton, Hugo Lafayette Black, Stephen G. Breyer, Alan M. Dershowitz, William J. Donovan, William O. Douglas, Dwight D. Eisenhower, David E. Feller, Abe Fortas, Richard N. Gardner, Conrad N. Hilton, Hubert H. Humphrey, Lyndon B. Johnson, Edgar F. Kaiser, Max M. Kampelman, Freda Kirchwey, Philip M. Klutznick, Benjamin Landis, David J. Macdonald, John S. McCain, Golda Meir, Agnes Elizabeth Ernst Meyer, Abner J. Mikva, Newton N. Minow, David A. Morse, Daniel P. Moynihan, Yitzhak Rabin, James Roosevelt, Walter Reuther, Robert Shaplen, Simon Ernest Sobeloff, Harry S. Truman, Earl Warren, Jacob Joseph Weinstein, Simon Wiesenthal, and J. Skelly Wright.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Associate justice of the U.S. Supreme Court, U.S. secretary of labor, U.S. ambassador to the United Nations, and lawyer. Full name: Arthur Joseph Goldberg. Born 1908; died 1990.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bacon, Emery -- Correspondence; Bazelon, David L. -- Correspondence; Beichman, Arnold -- Correspondence; Benton, William, -- 1900-1973 -- Correspondence; Black, Hugo LaFayette, -- 1886-1971 -- Correspondence; Breyer, Stephen G., -- 1938- -- Correspondence; Dershowitz, Alan M. -- Correspondence; Donovan, William J. -- 1883-1959 -- Correspondence; Douglas, William O. -- 1898-1980 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Feller, David E. -- Correspondence; Flood, Curt, -- 1938-; Fortas, Abe -- Correspondence; Gardner, Richard N. -- Correspondence; Hilton, Conrad N. -- 1887-1979 -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Kaiser, Edgar F. -- Correspondence; Kampelman, Max M., -- 1920-2013 -- Correspondence; Kennedy, John F. -- 1917-1963.; Kirchwey, Freda -- Correspondence; Klutznick, Philip M., -- 1907- -- Correspondence; Landis, Benjamin L. -- Correspondence; MacDonald, David J. -- Correspondence; McCain, John S. -- 1911-1981 -- Correspondence; Meir, Golda, -- 1898-1978 -- Correspondence; Meyer, Agnes Elizabeth Ernst, -- 1887-1970 -- Correspondence; Mikva, Abner J. -- Correspondence; Minow, Newton N., -- 1926- -- Correspondence; Morse, David A. -- 1907- -- Correspondence; Moynihan, Daniel P. -- 1927-2003 -- Correspondence; Rabin, Yitzhak, -- 1922-1995 -- Correspondence; Roosevelt, James, -- 1907- -- Correspondence; Reuther, Walter, -- 1907-1970 -- Correspondence; Shaplen, Robert, -- 1917- -- Correspondence; Sobeloff, Simon Ernest, -- 1894-1973 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Warren, Earl, -- 1891-1974 -- Correspondence; Weinstein, Jacob Joseph, -- 1902- -- Correspondence; Wiesenthal, Simon -- Correspondence; Wright, J. Skelly -- Correspondence; United States. -- Department of Labor; United States. -- Office of Strategic Services; United States. -- President's Task Force on International Education; United States. -- Supreme Court; AFL-CIO.; Kaiser Industries Corporation; National School Volunteer Program; United Nations -- Officials and employees, American; United Steelworkers of America; Denver post (Denver, Colo. : 1901); Ambassadors' spouses -- United States; American newspapers -- Colorado -- Denver; Art; Baseball players; Cabinet officers' spouses -- United States; Constitutional law; Free agents (Sports); Governors -- New York (State) -- Election -- History -- 20th century; International relations